Liquid Crystal Light Modulators - Jaroszewicz, Leszek R. (Bentham Science Publishers, 2020)
This brief monograph provides reports on liquid crystal materials used for specific devices designed for industrial applications. The authors of each chapter present insights on the design and technical aspects of the manufacturing of advanced liquid crystal light modulators reflecting their experience in advanced liquid crystal materials science. Chapters in the book first introduce readers to the chemistry and basic materials science of liquid crystal light modulators with information important for practical situations such as custom manufacturing and material quality assessment (including t.